2021
DOI: 10.3390/biology10030228
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Genetic Variation in Blue Gourami (Trichogaster trichopterus) as a Model for Labyrinth Fish

Abstract: Markers of genetic variation between species are important for both applied and basic research. Here, various genes of the blue gourami (Trichogaster trichopterus, suborder Anabantoidei, a model labyrinth fish), many of them involved in growth and reproduction, are reviewed as markers of genetic variation. The genes encoding the following hormones are described: kisspeptins 1 and 2, gonadotropin-releasing hormones 1, 2, and 3, growth hormone, somatolactin, prolactin, follicle- stimulating hormone and luteinizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…An example of an exotic species found in Peru would be Trichopodus trichopterus (Pallas 1770), order Anabantiformes, family Osphronemidae, that was reported in Yarinacocha in 2016, in the La Restinga fishing area (MINAM 2021). This species is a tropical freshwater fish native to Southeast Asia, known as the three spot gourami, and has a specialized organ (organ labyrinth) that allows them to breathe oxygen from the air (Blank & Burggren 2014), helping them to adapt to an environment of low oxygen concentration in the water (Degani et al 2021). Specimens of this group were introduced in 1970 for ornamentation (Ortega et al 2007) and have been reported for the city of Iquitos (department of Loreto, Peru) (Meza-Vargas et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…An example of an exotic species found in Peru would be Trichopodus trichopterus (Pallas 1770), order Anabantiformes, family Osphronemidae, that was reported in Yarinacocha in 2016, in the La Restinga fishing area (MINAM 2021). This species is a tropical freshwater fish native to Southeast Asia, known as the three spot gourami, and has a specialized organ (organ labyrinth) that allows them to breathe oxygen from the air (Blank & Burggren 2014), helping them to adapt to an environment of low oxygen concentration in the water (Degani et al 2021). Specimens of this group were introduced in 1970 for ornamentation (Ortega et al 2007) and have been reported for the city of Iquitos (department of Loreto, Peru) (Meza-Vargas et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…When caviar costs are lower, this benefit is much larger [20]. The study focused on three important ESD technology indicators: 1) differences in male and female gene expression in various organs; 2) differences in gonad transcription (mRNA level) [17] [18] [27] [64]; 3) genome variation between males and females (DNA sequences) to discover molecular markers [16] [18] [19].…”
Section: Whole-genome Sex-based Variation and Gene Expression In Russ...mentioning
confidence: 99%
“…Collaborations with the Institute and its researchers cover different fields of agriculture, industry, and academia, through MIGAL's departments of Soil, Water and Environment, Molecular and Computational Biosciences and Biotechnology, Plant Sciences, Nutrition and Natural Products, and Northern R & D, which includes various research groups led and supervised by senior researchers. In this article, we will focus on MIGAL's research related to fish and aquaculture, i.e., research groups working directly or indirectly on the biology and physiology of fish and amphibians in water and agricultural biotechnology under specific field conditions in northern Israel and other regions of the country [4] [5] [6] (Figure 1). Research and development are focused on fish with global export marketing potential alongside import prevention [5].…”
Section: Introductionmentioning
confidence: 99%